Long-Chain Fatty Acid Oxidation Disorder Presenting With Metabolic Acidosis in a Preterm Infant (GAIMS Journal of Medical Sciences, 2026)
Long‐chain fatty acid oxidation disorders (LC‐FAODs) are rare autosomal recessive metabolic disorders caused by defects in mitochondrial β‐oxidation. They often present in infancy with hypoketotic hypoglycaemia, cardiomyopathy, hepatic dysfunction or sudden metabolic decompensation. We report a 33.5‐week gestation male neonate with birth weight 1.240 kg, born to non‐consanguineous parents, who presented in the first days of life with persistent metabolic acidosis, hyperkalaemia and hypocalcaemia despite normal blood glucose. Newborn screening by tandem mass spectrometry showed marked elevations of long‐chain acylcarnitines (C14, C14:1, C18) together with hydroxyacylcarnitines (C16‐OH, C18‐OH), a pattern suggestive of very‐long‐chain acyl‐CoA dehydrogenase (VLCAD) or mitochondrial trifunctional protein (TFP) deficiency. Simultaneously, urine organic acid analysis revealed a 55‐fold increase in 4‐hydroxyphenyllactic acid (4‑HPLA) and mild elevation of 4‑hydroxyphenylpyruvic acid (4‑HPPA), raising the possibility of concomitant tyrosinaemia or a mitochondrial disorder. Management with avoidance of fasting, continuous glucose infusion, and medium‐chain triglyceride (MCT) supplementation led to gradual biochemical improvement. This case illustrates the diagnostic complexity of metabolic screening in preterm infants and underscores the importance of integrating clinical context with metabolic data. Early recognition and dietary intervention in LC‐FAOD can significantly improve outcomes.